(3cTa GdUdUdI Yf hUa GdRdRdIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3gPg ahGFO eaUdI SejJ cTa GdUdUdI Yf hUa GdRdRdI eG hQO ai MbjbJgG s
(3BNQgG (B:s
(3EdGNQL Edjg aJNdU GdeOjfI hPdc jhe GdNdGU BNQ cJGH cTa GdUdUdI Yf hUa GdRdRdI hGddg JYGdi CYde HPdc s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1491s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(1027(3c(B) s
Keywords: (3GdeYGQa GdYGeIs